2017
DOI: 10.1007/978-3-319-47944-6_1
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency-Following Response: A Window into Human Communication

Abstract: of the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 46 publications
2
83
0
7
Order By: Relevance
“…28,51 We demonstrated that macaques share with humans the neurophysiological mechanisms to represent fast acoustic periodicities 51 by exhibiting a humanhomologous frequency-following response (FFR). 49 Important for the present discussion is the fact that human participants that can entrain with high precision to an external beat also show larger intertrial consistency of the FFR potential, [52][53][54] suggesting a partial overlap between auditory circuits underlying the FFR and neural circuits involved in beat entrainment. In addition, monkeys can also detect stimulus omissions occurring in an isochronous auditory pattern exhibiting a mismatch negativity (MMN) potential 28 (i.e., a differential cortical brain signal to a deviant event, embedded in a stream of repeated standard events).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…28,51 We demonstrated that macaques share with humans the neurophysiological mechanisms to represent fast acoustic periodicities 51 by exhibiting a humanhomologous frequency-following response (FFR). 49 Important for the present discussion is the fact that human participants that can entrain with high precision to an external beat also show larger intertrial consistency of the FFR potential, [52][53][54] suggesting a partial overlap between auditory circuits underlying the FFR and neural circuits involved in beat entrainment. In addition, monkeys can also detect stimulus omissions occurring in an isochronous auditory pattern exhibiting a mismatch negativity (MMN) potential 28 (i.e., a differential cortical brain signal to a deviant event, embedded in a stream of repeated standard events).…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, we have studied the encoding of auditory periodicity through scalp‐recorded evoked potentials while awake monkeys passively listened to periodic auditory stimuli with different levels of metrical hierarchy . We demonstrated that macaques share with humans the neurophysiological mechanisms to represent fast acoustic periodicities by exhibiting a human‐homologous frequency‐following response (FFR) . Important for the present discussion is the fact that human participants that can entrain with high precision to an external beat also show larger intertrial consistency of the FFR potential, suggesting a partial overlap between auditory circuits underlying the FFR and neural circuits involved in beat entrainment.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Recently, Kraus et al. () have shown that the midbrain electrophysiological responses of concussed athletes reflect impaired auditory processing (Kraus, Anderson, White‐Schwoch, Fay, & Popper, ). Specifically, the authors demonstrated that mTBI disrupts the processing of the fundamental frequency, a key acoustic cue for identifying and tracking speech, and consequently, understanding speech.…”
Section: Introductionmentioning
confidence: 99%